Kuasa Jejaring Kerabat dalam Praktik Politik Lokal Pedesaan (Kajian Antropologi Politik) - Devi Siswandani; Kuncoro Bayu Prasetyo (Universitas Padjadjaran, 2022)
This study examines the practice of village political leadership that has been dominated by a kinship network. A qualitative-ethnographic method was applied in this study to investigate kinship’s structure and network, and its role in the village leadership. Data were collected through interview and observation. The study finds that the kinship network has been centered at the village head. This network has been deeply rooted and maintained over generations; and it has been the important social capital to win the village election. The kinship network has been the reference for recruitment and selections of village officials, strengthens the legitimacy of the village head power, facilitates the procedures of bureaucracy, and secured village head’s policies. Furthermore, the kinship network has played a central role in legitimizing the political power of the village head. Through this network, the village leadership goes without turmoil. However, this type leadership has created a weak community participation in village governance.